Proposta de indicadores de desempenho de processo e qualidade para unidades produtoras de biodiesel do norte do estado de Mato Grosso - Rodrigues, Sergio Guaraci Prado (Universidade Federal de São Carlos, 2011)
Corporate management has been a major challenge due to the changes of behavior of society as a whole. Much has been discussed in relation to meeting the needs and expectations of customers, models are developed (BSC, Sink and Tuttle, Performance Prism among others) in order to integrate the internal and external perspectives and approaches to organizations in order to facilitate understanding and measurement of an increasingly selective market and increasingly agile changes. Among these concerns is the issue of greenhouse gas emissions, the impact of ozone mainly by the use of fossil fuels (petroleum), besides the risk of its scarcity. Thus, research has been conducted in the area of renewable biofuels, such as ethanol, biodiesel, and other bioenergy sources. In these studies, has been shown to be economically viable, but mostly, the feasibility from the viewpoint of decreasing the rate of air pollution, greenhouse gas emissions by the use of biodiesel added to diesel used for transport. Because the biodiesel production process still developing industries with processes still under implementation, early production and / or stage of process improvement, usually with initial concern in technical procedures, variables of financial order, the early production, the soon return of investment, achieving the goals established in the strategic planning, among others, let aside a major issue: the measurement and evaluation of process performance in terms of quality and productivity. In this respect, the need arises for indicators measuring the performance of processes and products of unit producing biodiesel. Thus this dissertation discusses methods, tools and indicators of process performance, with an emphasis on quality and productivity, from the "needs" of the internal users of the company, as well as existing legal requirements. The study of multihulls, with interviews and observations "in situ" with three units producing biodiesel from the northern region of the state of Mato Grosso, supported by semi-structured questionnaire was used as the research method. From tabulation, analysis and compilation of data, have been proposed measurement indicators appropriate to the reality and needs of managers performance.
Proposal of indicators of process performance and quality for biodiesel production units in northern Mato Grosso
Keywords: Sistemas de medição de desempenho; Indicadores de desempenho; Qualidade; Produtividade; Biodiesel; Performance Indicators; Performance Measurement; Quality and Productivity; Biodiesel; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO